LCOE at risk in different locations in Colombia - Mican, Camilo; Martínez-Ruiz, Yessenia; Manotas-Duque, Diego Fernando (International Journal of Sustainable Energy Planning and Management, 2025)
The development of renewable energy (RE) projects is closely tied to the financial attractiveness of these investments. Despite the extensive literature, most studies focus on a static analysis, which is no longer adequate for dealing properly with the uncertainty associated with RE projects. This study proposes a stochastic model based on the levelized cost of energy (LCOE) and the application of VaR (value at risk) and CvaR (conditional value at risk) measures for risk assessment. Using a hypothetical case consisting of a solar farm with a rated capacity of 10 MWp, the analysis was conducted for nine Colombian municipalities. The irradiation levels at each site were considered the sole source of uncertainty. In addition, the Colombian regulatory framework was considered, represented by accounting and tax benefits. The results obtained from this work made it possible to evaluate the effect of resource behavior on the financial risk level of PV projects. The results provide a ranking of the nine assessed municipalities from a financial point of view and highlight the influence of considering solar resources as a risk factor on the project´s financial expected performance.